Evaluation of patients with multiple sclerosis and sleep disorders - Bavli, Songül; İnanç, Yılmaz; Tuncel, Deniz (Journal of Surgery and Medicine, 2021)
Background/Aim: Sleep disorders are often reported by MS patients and various studies have shown sleep disorders to be more widespread in MS patients than in healthy control groups. However, despite the high frequency, they are often overlooked. This study aimed to determine the characteristics of fatigue and daytime sleepiness in MS patients, the underlying factors, and their relationship for testing the reliability of subjective scales and establishing when patients presenting with these symptoms should be referred to a sleep specialist. Methods: The patients enrolled in this cohort study were aged >18 years, had a confirmed diagnosis of relapsing remitting MS, were in the remission phase, had not taken steroids within the last 3 months, and had complaints of fatigue, daytime sleepiness, and sleep disorders. Patients with EDSS score <3 were admitted to the sleep laboratory for 2 days to perform 1 night of polysomnography (PSG) and a 5-nap multiple sleep latency test (MSLT) the following day. The results were evaluated with regards to the clinical scales. Results: A total of 41 patients were evaluated. Excessive daytime sleepiness was found in 14 (34.1%), and sleep quality was poor in 28 (68.29%). According to the PSG-MSLT, a sleep disorder was found in 37 patients (90.24%). A diagnosis of hypersomnolence was made in 23 (56.1%) patients, and two (4.88%) were categorized as type 2. Conclusion: It is necessary for every clinician involved in MS treatment to correctly diagnose and treat fatigue, excessive daytime sleepiness, and other sleep disorders, which increase the disability of disease. When the high prevalence of these types of disorders and the fact that they are multifactorial are taken into consideration, the timing of the referral of these patients to a sleep specialist and the implementation of objective tests become more important.